Positive emotional stimuli in teaching foreign language vocabulary. (February 2022) - Kralova, Zdena; Kamenicka, Jana; Tirpakova, Anna
Abstract: Positive emotional stimuli, when compared to neutral memories, persist longer in memory and are recalled with greater accuracy and readiness, which might be rather significant in foreign language learning. The primary objective of this study was to determine whether or not positive emotional stimuli enhance remembering of new foreign language vocabulary. The pre-test/post-test design was applied, and both declarative and procedural vocabulary knowledge were tested in control and experimental groups before and after the intervention. Participants՚ emotional comfort and foreign language enjoyment were evaluated by two standardized scales and their perception of the intervention was investigated through a feedback questionnaire. The findings revealed a significant increase of declarative vocabulary knowledge and foreign language enjoyment in the experimental group. Highlights: Positive emotional stimuli persist longer in memory than neutral memories. Can positive emotional stimuli enhance remembering of foreign language vocabulary? Both declarative and procedural vocabulary knowledge was tested in the experiment. Participants՚ emotional comfort and foreign language enjoyment were evaluated. Declarative vocabulary knowledge and foreign language enjoyment increased.